Vaccination of pigs reduces Torque teno sus virus viremia during natural infection. Issue 30 (9th July 2015) - Jiménez-Melsió, Alexandra; Rodriguez, Fernando; Darji, Ayub; Segalés, Joaquim; Cornelissen-Keijsers, Vivian; van den Born, Erwin; Kekarainen, Tuija
Highlights Vaccination against TTSuVk2a resulted in a delay and lower viral load in immunized pigs. Vaccinated pigs were seroconverted against TTSuVk2a proteins. A combination of DNA and protein immunization can control TTSuVk2a viremia.